BUILDING CONTROL SYSTEM TARGET NILAI IPK DENGAN METODE FORWARD CHAINING - Padeli Padeli; Aris Martono; Fadli Fadillah Rahman (CCIT Journal, 2015)
An institution if it is to continue to achieve the target it is necessary to continue working, in this case that needs to be realized by the students during the tasting of science education in junior college from start to finish is a high IPK, as a measure of academic success. But it was necessary to achieve a high IPK in the target, appears to be less satisfactory if graduated from an institution with a low IPK. Be aware that a high IPK is one of the factors contributing to a career or to pursue higher degrees. However, until now the majority of applications only use instasi educational standards of judgment that can only display the values directly in the absence of tools as an experiment. It is necessary to build an expert system control program IPK as a tool for students. Expert systems or knowledge that is often known as the Base System aims to help motivate and analogize the stages of how to work the program the system uses forward chaining reasoning method that will be able to control the resulting IPK according to the expected target information and prevention solutions that need to be done to achieve target.of such information would provide information that the target has been reached or not. If the target is achieved then you reach your target information, and vice versa if it fails then it will appear warning you that the target is not reached. The cause of not achieving the target would appear that the solution must be reached, the expert system will provide a list of the red line on the value that corresponds to it, another solution could be done by changing the maximum standard